Time, Change, and Continuity: The Role of Historical Consciousness in Social Studies Education for Shaping Student Identity - Inoki Ulma Tiara; Maisya Mariska; Elisa Saputry (Yayasan Dekhalisha Global Prestise, 2026)
This research examines the role of time, continuity, and change concepts in Social Studies (IPS) education, particularly history learning, and their relationship with student identity formation, social dynamics, and young generation's perspectives toward the past. History education is expected to foster national identity, critical thinking abilities, and historical consciousness. However, in practice, history learning often becomes trapped in fact and date memorization, disconnected from students' current reality, resulting in low interest in learning history. This study employs a qualitative descriptive approach with emphasis on document analysis (IPS curriculum, textbooks, and scientific literature), which can conceptually be enriched through interview and observation techniques in history learning. The theoretical framework relies on concepts of time, continuity, and change in history; the nature of IPS education as integration of social sciences; and various philosophies of history education (perennialism, essentialism, humanism, and social reconstruction). Findings indicate that history contributes significantly to student identity formation through collective national narratives and shared historical experiences. Understanding continuity and change helps students read social dynamics: what changes and what persists in society. Students' perspectives toward the past are influenced by formal education, family memory, media narratives, and quality of historical literacy in the digital era. While the Indonesian IPS curriculum incorporates dimensions of time, continuity, and change, classroom implementation often remains textual and memorization-oriented. The main challenges in history learning include low student interest, monotonous methods, gaps between official narratives and critical perspectives, and information floods (including historical distortions) in digital media. This research recommends strengthening more interactive, contextual, and critical IPS learning through inquiry approaches, projects, digital media utilization, and local history integration, ultimately forming a young generation with historical consciousness, strong identity, and ability to wisely comprehend social changes.